Religious Contestation between Christian and Muslim Community in the 'Gospel City' of Manokwari Papua - Farno Billy Arthur Gerung; Rahman Mantu (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
This article discusses the dynamics of the relationship between Papuan Muslims and Christians as the majority population. Part of the dynamic is the disharmony between the two religious adherents due to several reasons; construction of facilities for worship, namely mosques that are increasingly massive, fighting over each other for public space, domination of the bureaucracy by Christian elites, the economic sector, and strengthening of identity through the performance of religious symbols. Until its peak, the Local Regulation for the spiritual development of Manokwari emerged as the Gospel city. Qualitatively, this article describes and identifies ethnographically how the contestation between Muslims and Christians, the clash between the two, and the debate on the issue of local regulations of the Gospel. Some of the conclusions of this article find that the majority group feels that Papua has historically been the center of Christianity and the efforts to care for it are so strong, this is in line with the impact of what is happening outside Papua such as the many sharia regulations that are widely applied in Java and Sumatra areas.